2003
DOI: 10.2527/2003.8161499x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine, blood metabolite, and meat quality changes in goats as influenced by short-term, preslaughter stress1

Abstract: The purpose of this study was to determine the effects of short-term, preslaughter stress on physiological responses and meat quality in goats of different age groups. The goats (n = 28) were classified into young (6 to 12 mo of age) and old (24 to 30 mo of age) groups, feed deprived overnight, and slaughtered at three different times (replicates). On each slaughter day, goats were either subjected to a 2-h transportation stressor (TS) or remained unstressed in holding pens (NS) before slaughter. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
100
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 28 publications
18
100
2
9
Order By: Relevance
“…Kadim et al (2006) observed that the meat of goats was darker and characterized by higher contribution of redness and lower contribution of yellowness (lower values of L* and b*, higher values of a*) after 2 h of transport in comparison with the meat of non-transported animals. Similar results were reported by Kannan et al (2003) in a study on goats. In a study by Kadim et al (2009), transport had no significant influence on the colour parameters of lamb meat.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Kadim et al (2006) observed that the meat of goats was darker and characterized by higher contribution of redness and lower contribution of yellowness (lower values of L* and b*, higher values of a*) after 2 h of transport in comparison with the meat of non-transported animals. Similar results were reported by Kannan et al (2003) in a study on goats. In a study by Kadim et al (2009), transport had no significant influence on the colour parameters of lamb meat.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were reported in goats after 2 h of transport (Kadim et al, 2006) and in lambs which were slaughtered after 75 min of transport and a short rest period (Ekiz et al, 2012a). In contrast, Apple et al (1995) reported lower shear force values in the meat of lambs subjected to pre-slaughter stress in comparison with the control group, whereas Kannan et al (2003) did not report any differences in the hardness of meat from transported and non-transported goats.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…observed the main increase in plasma cortisol level during the first 90 min of journey in sheep. Similarly Kannan et al (2003) found that the cortisol concentrations increased markedly within 1-h after the beginning of transportation in goats.…”
Section: Blood Constituentsmentioning
confidence: 91%